Democratization of Post-Taliban Afghanistan: prospects and challenges - Ra'ees, Wahabuddin (2017)
The 2001 US invasion of Afghanistan entailed combating terrorist cells and democratization of Afghanistan. The democratization argument has been based on the assumption that Afghanistan had no history of civic culture and democratic experience. Afghanistan’s history was that of authoritarianism, dictatorship and dogmatic leadership. On December 5, 2001, Afghan groups signed the UN-sponsored Bonn Agreement to make Afghanistan a democratic nation. Yet of late some argue that the lukewarm democratization of the country and failure of democratic experience to instil civic culture indicate that the real signatories were powerful states with vested interest in collaboration of their Afghan allies. As mandated in Bonn Agreement, Afghanistan promulgated a new constitution, laws on political parties and elections, registered political parties, held presidential and parliamentary elections and established an Independent Election Commission. The democratization of Afghanistan initiated by the Bonn Agreement also entailed the development of a multi-ethnic and an ideologically diverse party politics and party system and the role of women. Academics argue that Afghanistan will be an ideologically split and ethnically divided polity, democratization of the Afghan society has a moderating impact, containing the negative affect of ethnic cleavages and ideological differences so characteristics of the Afghan political culture at a manageable level. But, the question that may be raised is that why have not promulgation and introduction of the Bonn mandated democratic institutions led to institutionalization of democracy and civic culture in Afghanistan? Success of democracy in Afghanistan depends on its institutionalization. Afghanistan lacked political will and leadership to institutionalize democracy. It has found the political will in the person of President Ashraf Ghani. Will the signatories of the Bonn Agreement and their foreign backers cooperate to allow Afghanistan become a functioning democracy?